Quadricuspid aortic valve in pregnancy: a case discussion - Saidhandapani, Kalyani; Goswami, Neelam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
A quadricuspid aortic valve (QAV) is an exceptionally rare congenital heart anomaly first time identified in 1862. This condition involves the presence of four cusps in the aortic valve instead of three, leading to potential complication such as aortic regurgitation. In the reported case 29-year-old pregnant women at 29 weeks gestation presented in OPD for further follow up with no dyspnea on exertion. Electrocardiogram findings were normal and transthoracic echocardiography (TTE) revealed a QAV with three equal sized cusps and one smaller cusp accompanied with mild aortic regurgitation with no other additional anomalies observed. The patient underwent a normal vaginal delivery without any peripartum cardiac complications. While QAV is a rare congenital anomaly it is not uncommon to be associated with aortopathies. This condition makes pregnancy is in high-risk state. Close monitoring especially in second and third trimesters remains of utmost importance. Due to its rarity, the characteristics, natural history, and long-term outcomes of QAV are poorly defined. In general, aortic valve disease during pregnancy can be associated with higher maternal and fetal risks. Pre conceptional counselling is essential to assess and manage high these risks appropriately. For instance patient with significant AVD should be assessed and followed up by multidisciplinary team including cardiologists, obstetricians, cardiothoracic surgeons and anasthesiae both before and throughout pregnancy. In summary, while QAV is a rare congenital anomaly its association with pregnancy necessitates careful monitoring and management to ensure favorable outcomes for both mother and child.